Identification of glucuronidation and biliary excretion as the main mechanisms for gossypol clearance: in vivo and in vitro evidence. (20th February 2014) - Liu, Hongming; Sun, Hua; Lu, Danyi; Zhang, Yuchen; Zhang, Xingwang; Ma, Zhiguo; Wu, Baojian
Abstract: 1. The natural polyphenol gossypol possesses many therapeutic benefits. Here we aim to determine the elimination pathways of gossypol in vivo and in vitro . 2. Metabolite elucidation of gossypol was performed using UPLC-QTOF/MS coupled with Metabolynx analysis. Clearance of gossypol was evaluated in bile duct cannulated rats and in the single-pass perfused rat intestine model. In vitro glucuronidation of gossypol was characterized using liver and intestine microsomes as well as recombinant UDP-glucuronosyltransferase (UGT) enzymes. 3. Analysis of rat plasma, urine, and feces revealed glucuronidation as the only metabolic pathway for gossypol. In bile duct cannulated rats, considerable amounts of glucuronides (G1, G2 and G3; 58.8–83.2% of dose) and parent compound (5.0–20%) were excreted into bile after IV administration. In the perfused rat intestine model, gossypol was well absorbed with a\def\newpage{\vfill \break } \nopagenumbers $ {\rm P}_{{\rm eff}}^{*} $ \newpage \end (the dimensionless effective permeability) value of 4.4. Significant amounts of glucuronides (G1, G2 and G3) were excreted into the gut lumen (2.5%) and into the bile (4.8%). Biliary excretion of unchanged gossypol (6.0%) was comparable to that of glucuronides. Further, gossypol was subjected to rapid glucuronidation by liver and intestine microsomes. Reaction phenotyping showed that multiple UGT1A enzymes (including UGT1A1, 1A3, 1A7 and 1A8) are mainly responsible for gossypol metabolism. 4. In conclusion, glucuronidation was the only metabolic pathway for gossypol in rats. Excretion of unchanged gossypol into bile was also an important clearance mechanism.